SEEDLING NATION’S CHARACTER THROUGH LEARNING HISTORY: LEARNING FROM EXILE CAMP OF BOVEN DIGOEL, PAPUA - Hamid, Abdul rahman (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2013)
This article explains about the history of Boven Digoel Camp in its correlation with the formation of nation’s character. From 1927 to 1930s, colonial government had been exiling politic internees there. The aims is to control their thought and attitudes towards the government. During the exile, there were two diverse characters found, as the result, there were two groups of internees found, there who change their attitudes toward the governement and those who were consistent with their political attitudes.The change was very pragmatic; it was done in order to survive in the camps and with expectation to return to their hometowns safety. However, camp life had formed solidarity and diversity spirit among the internees who came from diverse region, ethnic, language and religion. Personal, ethnical, and political view point were gradually squeezed at one place. The ideal to be a nation was increasingly strengthened particularly when they were confronted to the discriminative policies of colonial administration. These various experiences were worthy lessons for us to reflect the transformation process of our nation, Indonesia which had scarcely and expensively paid by the internees which can serve as a source of curriculum content of historical education.